HUBUNGAN ANTARA KETEGUHAN GESER DENGAN KETEGUHAN REKAT INTERNAL PAPAN PARTIKEL - Paribotro Sutigno; I M Sulastiningsih (Pusat Penelitian dan Pengembangan Hasil Hutan, 1992)
One of the partideboard properties that must be tested is internal bond strength or tensile strength perpendicular to surface. the testing procedure is relatively difficult because before applying a tension load vertically to the board face, the specimen must be adhere to steel or wood blocks for seuerol hours to obtain good adhesion. To simplify the pro- cedure, the use of another testing procedure called shear strength test was tried. It is found that there is a relationship between shear strength (X) and internal bond strength (Y) which can be expressed by linear regression equations i.e,: Y = - 0.105 + 0.180 X for interior particleboard and Y = - 0.925 + 0.398 X for exterior particleboard. The interior particleboard specimens were tested under dry condition whereas exteriorparticleboard specimem were boiled for two hours before testing. Both regression equations can not be pooled, Based on the result it can be cohcluded that internal bond strength of particleboard can be estimated by using its shear strength value.